Loneliness and isolation among people with dementia and their carers: Prevalence, risk factors and a dyadic analysis: Psychosocial factors and environmental design / Social networks. (7th December 2020) - Rippon, Isla; Victor, Christina R; Quinn, Catherine; Martyr, Anthony; Matthews, Fiona E; Clare, Linda
Abstract: Background: People with dementia and their carers may be vulnerable to loneliness and isolation. We investigated: (a) prevalence of, and risk factors for, loneliness and isolation among people with dementia and their carers and (b) the interrelationship between loneliness and isolation for dyads (person with dementia and carer). Method: The IDEAL cohort of people with dementia and their carers includes two loneliness measures: the 6 item de Jong Gierveld (DJG) scale (range 0‐6 and classified: not lonely (0‐2), moderately lonely (3‐4) and severely lonely (5+)) and a single‐item question, plus a measure of social isolation, the six‐item Lubben social network scale (range 0‐30: not isolated (13+) or isolated (12 or less). For dyads consisting of a carer and a person with dementia, 1089 had complete data on loneliness and 1204 on social isolation. We report prevalence and examine loneliness/isolation risk factors using regression analysis for people with dementia and carers separately. We use Actor‐Partner Interdependence Models (APIM) to examine the relationship between isolation and loneliness within dyads and vice‐versa. Result: Prevalence of severe loneliness for people with dementia was 10% (single item score) and 5% (DJG score 5+) (15% and 18% respectively for carers). One third of people with dementia, 35%, were at risk of isolation (18% of carers). Social isolation was the only risk factor for loneliness consistent for both carers and people with dementia. Risk factors for loneliness in carers were caregiving stress and relationship quality and in people with dementia living alone, depression and life satisfaction/quality of life. Loneliness ratings were congruent in 43.1% of dyads (67.8% for isolation). Dyadic analysis using APIM demonstrates that loneliness is affected by both individuals' own isolation and that of their partners.There were also actor and partner effects for the association between loneliness and isolation. Conclusion: Most people with dementia and their carers are neither lonely nor isolated. Risk factors for loneliness are different for carers and people with dementia. Isolation in the carers influences the loneliness of the person with dementia and vice versa.